The use of anti-TNFα medications for rheumatologic disease in pregnancy - Megan EB Clowse (Dove Medical Press, 2010)
Megan EB ClowseDivision of Rheumatology and Immunology, Department of Medicine, Duke University Medical Center, Durham, NC, USAAbstract: Anti-TNFα medications have led to vast improvements in the treatment of inflammatory conditions, including rheumatoid arthritis and Crohn’s disease. As these diseases often afflict women in their reproductive years, the safety of these drugs during pregnancy is an important issue. Prospectively collected data thus far appear to be reassuring; however an analysis of the FDA-reported anomalies has raised some questions. It appears that significant levels of these drugs cross the placenta as the pregnancy nears term, but little is passed through breast milk. Prior to using these medications during pregnancy, the risks and benefits of these drugs, other treatment options, and the ongoing inflammatory condition all must be carefully weighed by both doctor and patient.Keywords: pregnancy, anti-TNFα medications, rheumatoid arthritis, Crohn’s disease, teratogenesis